FTO O-GlcNAcylation promotes TRIM21-mediated FTO ubiquitination degradation to sustain the negative feedback control of macrophage inflammation - Zhang, Lu; Liu, Min; Xie, Yan; Yuan, Bi-Feng; Peng, Zhiyong; Xiong, Jun; Zhang, Xiao-Lian (Frontiers in Immunology, 2025)
IntroductionThe fat mass and obesity-associated protein (FTO), a key RNA N6-methyladenosine (m6A) demethylase, has been highlighted for its important role in inflammatory response. Emerging evidences link the O-GlcNAcylation to numerous human diseases, particularly inflammation. However, the specific role and underlying mechanism of FTO O-GlcNAcylation in inflammation remain elusive.MethodsThe FTO O-GlcNAcylation modification was determined by co-immunoprecipitation (Co-IP) assay, metabolic glycan labeling combined with click reaction, and liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis. Chromatin immunoprecipitation (ChIP)-qPCR and dual-luciferase reporter assay were used to determine FOXO1 binding to the Gfat2 promoter and the Gfat2 promoter activity during LPS stimulation. The FTO ubiquitination modification and the interaction between FTO and TRIM21 were detected by confocal microscopy, pull-down, and mass spectrometry analysis. The effects of FTO O-GlcNAcylation on the ubiquitination degradation of FTO were assessed by Co-IP and protein stability assays. The Socs1 mRNA m6A methylation levels were detected by m6A-RNA-immunoprecipitation (RIP)-qPCR. The myeloid-specific Fto deletion (myeFto-/-) mice, the macrophage depletion and reconstitution experiments, and enzyme-linked immunosorbent assays (ELISA) were used to evaluate inflammatory responses in Salmonella Typhimurium (S. Typhimurium) or bacterial endotoxin (lipopolysaccharide, LPS) induced sepsis mouse models.ResultsWe demonstrate that FTO undergoes O-GlcNAcylation specifically at the serine 95 (Ser95) site. LPS enhances FTO O-GlcNAcylation modification levels by increasing the FOXO1-regulated GFAT2 expression. O-GlcNAcylation of FTO promotes TRIM21-mediated K48-ubiquitination degradation of FTO, which further induces suppressor of cytokine signaling (Socs) 1 m6A methylation, thus sustains SOCS1 protein expression and suppresses multiple inflammatory cytokines IL-1β/IL-6/TNF-α production in LPS-stimulated macrophages. FTO O-GlcNAcylation mutation (S95A) aggravates S. Typhimurium or LPS-induced sepsis, while FTO O-GlcNAcylation suppresses the hyperinflammatory phenotype in mice. Promotion of O-GlcNAcylation by an OGA inhibitor Thiamet-G alleviates LPS-induced inflammatory responses and septic shock in mice.ConclusionThese findings reveal a mechanism that FTO O-GlcNAcylation promotes its ubiquitination degradation, and thus induces Socs1 m6A methylation and downregulates LPS-mediated inflammatory response, which maintains the negative feedback control of macrophage inflammatory cytokine storm in sepsis. Regulation of FTO O-GlcNAcylation may offer a potential therapeutic strategy for combating endotoxin-induced inflammatory disease and other FTO abnormal expression-associated diseases.